2014
DOI: 10.1111/j.1600-0587.2013.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in clutch size–lay date regressions in Tachycineta swallows: effects of food supply or demography?

Abstract: In a study of almost 16 000 nest records from seven swallow species across the entire Western Hemisphere, clutch sizes decline with relative laying date in each population, but the slope of this decline grows steeper with increasing distance from the equator. Late-laying birds at all latitudes lay clutches of similar sizes, suggesting that latitudinal differences may be driven primarily by earlier-laying birds. Focused comparisons of site-years in North America with qualitatively different food availability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 36 publications
2
33
1
2
Order By: Relevance
“…This is consistent with the results of a study across the entire Tachycineta genus that demonstrated that the slope of the decline in clutch size with laying date varies across the Western Hemisphere, being less steeply negative in populations breeding closer to the equator (Winkler et al . ). A similar pattern was also found in the House Wren Troglodytes aedon , another widely distributed, single‐brooded passerine (Young ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is consistent with the results of a study across the entire Tachycineta genus that demonstrated that the slope of the decline in clutch size with laying date varies across the Western Hemisphere, being less steeply negative in populations breeding closer to the equator (Winkler et al . ). A similar pattern was also found in the House Wren Troglodytes aedon , another widely distributed, single‐brooded passerine (Young ).…”
Section: Discussionmentioning
confidence: 97%
“…It is also similar between first‐year and older females (Winkler & Allen ), and is not affected by variation in local food abundance (Winkler et al . ). Such consistency provides further support for the possibility that the rate of seasonal decline in clutch size may be facilitated by the seasonal dynamics of photoperiod.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The T-implanted females skipped egg laying for 2-4 days after initiating a clutch, while the ATD+F-implanted female continued to lay eggs; nevertheless all four females were included in subsequent analyses because the effects of silastic implants on T and aromatase activity can be detected within a day of being implanted (see Smith et al, 1977;Balthazart et al, 1990). I tested whether clutch size and average egg mass differed among females in each treatment using separate analysis of covariance (ANCOVA) for each variable that included clutch initiation date as a covariate to control for the seasonal decline in clutch size that occurs in tree swallows (Winkler et al, 2014). I used a z-transformation to center and scale clutch initiation date so that the effect of treatment on clutch size or average egg mass could be interpreted in the presence of a treatment x initiation date interaction (Schielzeth, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…I also tested whether clutch size and average egg mass differed by the plumage brightness treatment of the female. I included year as a categorical variable and standardized clutch initiation date as a covariate to control for the seasonal decline in clutch size that occurs in tree swallows (Winkler et al, 2014). For these analyses, I used the R package lmerTest (Kuznetsova et al 2016) to calculate P values for fixed factors and covariates.…”
Section: Discussionmentioning
confidence: 99%